'And Then He Switched off the Phone': Mobile Phones, Participation and Political Accountability in South Sudan's Western Equatoria State. Issue 1 (9th March 2015) - Schomerus, Mareike; Rigterink, Anouk S.
This paper uses qualitative and quantitative original data to investigate the impact of mobile phones in situations of political contestation or conflict. We derive hypotheses from theories in general political science, and on the role of mobile phones specifically. These suggest that a link exists between access to better communication structures, political participation and government accountability. Given such a link, information and communications technologies—specifically mobile phones—could play a positive role in building a more accountable government, and with that, contribute to statebuilding. We examine to what extent these hypotheses hold true for ordinary citizens in South Sudan's Western Equatoria State (WES). Using interdisciplinary methods, we use data gathered through in-depth interviews and a quantitative survey and find little evidence that mobile phone coverage contributes to statebuilding or peacebuilding through a causal link between information, voting, political participation and government accountability. In a situation where administrative structures and mechanisms do not exist for citizens to hold politicians accountable, access to mobile phones might mean greater dissatisfaction with political participation and voting. People living in areas without coverage expressed a deep mistrust of government, and appeared to want to withdraw from the system of government entirely.